PENERAPAN STS DI DESA DAYA TARIK MUSIK KOTA AMBON MEMBERDAYAKAN GANDARIA ENDEMIK MALUKU - Papilaya, Pamella Mercy; Sinay, Hermelina; Karuwal, Ritha (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
Application of science-technology-society (STS) in the village of Ambon City Music Attraction through empowerment of Gandaria (Bouea macrophylla) Maluku Endemic Plants. Community service is participatory in nature, namely the method of strengthening community capacity is not in the form of training but increases knowledge and skills that are normative. The service is carried out in Amahusu village as a tourist attraction village in Ambon city. The subjects in this service activity consisted of Mrs. PKK, and teenagers in Mahahusu village. The products produced include 6 snacks and beverages, namely: Yogurth, Nata, Wine, Dodol, Boble Tea, and Jelly drinks. Organoleptic test on color, aroma, texture, taste, and acceptability. This service program has changed the culture of the community into producing products. In addition to the ability of the program, it is hoped that the community will be more independent and just